Differences in training load, jump performance and injury occurrence in elite youth volleyball players - Bouzigues, T.; Candau, R.; Philippe, K.; Maurelli, O.; Prioux, J. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: External and internal training load are used to monitor training effects in volleyball. Occurrence of injuries in volleyball is dependent of training loads and state of fitness but also playing positions and gender. This study aims to investigate the impact of gender and playing positions on injury occurrence among young volleyball players, considering both training loads and fitness levels. METHODS: Conducted from September 2021 to May 2022, this study involved 37 elite young volleyball players, comprising 16 female (176.8±3.6 cm; 65.3±5.7 kg; 13.9±1.1 years old) and 21 males (189.6±7.3 cm; 77.4±9.5 kg; 14.7±1.2 years old). G-Vert accelerometer was used to quantify training load. During these sessions, RPE, state of fitness and occurrence of injuries, were collected using a daily questionnaire. RESULTS: The primary findings indicate that males demonstrated a higher number of jumps, mean intensity, mean training load per session, and reported higher fitness levels compared to females (P<0.001). However, females were more injured than males (P<0.001). Setters were identified as the players with the highest jump frequency, albeit at lower heights and intensities than their counterparts (P<0.001). Among males, middle blockers exhibited the highest mean intensity and training load per session (P<0.01). CONCLUSIONS: The elevated frequency of injuries and a worse reported fitness levels among females, despite lower training loads, suggests a potential deficiency in physical preparation among young women, particularly in terms of their ability to perform repeated high-intensity jumps.